Anaemia in chronic kidney disease patients treated with darbepoetin α. Issue 2 (12th March 2012) - Mejía, M.; Flor, A.; Escudero, A.; Mulet, A.; Llopis, P.; Barreda, D.
Abstract : Background: FDA and EMEA recommend haemoglobin (Hb) values above 10 g/dl without exceeding 12 g/dl in patients with chronic kidney disease (CKD) treated with darbepoetin α (Dα) in order to avoid cardiovascular risk. Purpose: To analyse the adherence to the FDA and EMEA recommendations for the use of Dα in the treatment of anaemia in CKD patients. Materials and methods: Retrospective study of CKD patients who were dispensed Dα at the outpatient area of the Pharmacy Department during August–September 2011. Inclusion criteria: patients in treatment with Dα at least during 6 months. The authors evaluated Dα dosage and Hb level in the last four dispensations and identified patients with Hb out of range (10–12 g/dl). Data collected: number of total dispensations, Hb levels in each dispensation, Dα monthly dosage and changes in prescription if Hb level was out of range. Results: 90 patients were treated with Dα, but only 52 fulfilled the inclusion criteria. 59.6% were women, the median age was 78. 76.9% were out of the recommended range. The average of maximum and minimum Hb recorded in this group was 12.7±0, 2 g/dl and 10.4±0, 7 g/dl, respectively, with a mean dose of 88±12 mcg/month throughout the study period. 160 dispensations were made to this group, 43.1% were associated with Hb out of range, carrying out changes at prescription in 26.1%. Patients who had changes in the prescription had a maximum Hb of 12, 9±0, 5 g/dl and a minimum of 8, 8±1, 1 g/dl, while the rest, maximum and minimum Hb was 12.8±0.3 g/dl and 9.1±0, 6 g/dl, respectively. Conclusions: Changes in prescriptions respond to levels below the recommended interval, while levels outside the upper limits were not modified, so it seems necessary to establish a protocol to guarantee the security of the treatment. Pharmacists could play an important role in controlling laboratory parameters and Dα dosage in order to reduce the number of patients with Hb levels out of range.